Acute Kidney Injury in the Age of Enhanced Recovery Protocols. Issue 8 (August 2018) - Hassinger, Taryn E.; Turrentine, Florence E.; Thiele, Robert H.; Sarosiek, Bethany M.; McMurry, Timothy L.; Friel, Charles M.; Hedrick, Traci L.
Abstract : BACKGROUND: Acute kidney injury is a prevalent complication after abdominal surgery. With increasing adoption of enhanced recovery protocols, concern exists for concomitant increase in acute kidney injury. OBJECTIVE: This study evaluated effects of enhanced recovery on acute kidney injury through identification of risk factors. DESIGN: This was a retrospective cohort study comparing acute kidney injury rates before and after implementation of enhanced recovery protocol. SETTINGS: The study was conducted at a large academic medical center. PATIENTS: All of the patients undergoing elective colorectal surgery between 2010 and 2016, excluding patients with stage 5 chronic kidney disease, were included. MAIN OUTCOME MEASURES: Patients before and after enhanced recovery implementation were compared, with rate of acute kidney injury as the primary outcome. Acute kidney injury was defined as a rise in serum creatinine ≥1.5 times baseline within 30 days of surgery. Multivariable logistic regression identified risk factors for acute kidney injury. RESULTS: A total of 900 cases were identified, including 461 before and 439 after enhanced recovery; 114 cases were complicated by acute kidney injury, including 11.93% of patients before and 13.44% after implementation of enhanced recovery ( p = 0.50). Five patients required hemodialysis, with 2 cases after protocol implementation. Multivariable logistic regression identified hypertension, functional status, ureteral stents, nonsteroidal anti-inflammatory drugs, operative time >200 minutes, and increased intravenous fluid administration on postoperative day 1 as predictors of acute kidney injury. Laparoscopic surgery decreased the risk of acute kidney injury. The enhanced recovery protocol was not independently associated with acute kidney injury. LIMITATIONS: The study was limited by its retrospective and nonrandomized before-and-after design. CONCLUSIONS: No difference in rates of acute kidney injury was detected before and after implementation of a colorectal enhanced recovery protocol. Independent predictors of acute kidney injury were identified and could be used to alter the protocol in high-risk patients. Future study is needed to determine whether protocol modifications will further decrease rates of acute kidney injury in this population. SeeVideo Abstract athttp://links.lww.com/DCR/A568 . Abstract : Supplemental Digital Content is available in the text.